(untitled) (Eurasian Journal of Religious Studies, 2021)
The article deals with the peculiar hagiological character of the narrative genre contributes to the formation of sacredness as an important part of the sanctity of the saint, portrays the hero as a miracle-working, inaccessible to ordinary people, is aimed at creating impressions, strengthening faith in the saint. It is reported that there was a companion named Muhammad Ukkasha ibn Mihsin al-Asadi, who participated in the wars, became famous for his heroism, died in 632. At the heart of the story of Ukasha-Ata, a sacred place in the Turkestan region, it is proved that bullet impenetrability, sword impenetrability and beheadings during prayer, the motive of the severed head are repeated, stable motives associated with Khorasan-Ata, Arystan Bap, Masat-Ata and Shakpak-Ata and other saints. The impenetrable hero-Ukasha-ata is deceived by his enemies, who try to find out his vulnerability through a woman (a witch, sometimes his wife) and make an attempt - an ancient myth that is also noted in folklore and fairy tales. Only this event revived the religious character, portraying the hero as fighting on the path of the spread of Islam, the enemy-the enemies of religion. Ukasha ata is depicted as a God-fearing person who does not worry about anything during morning prayers, and when he is committed to slavery, his body is freed and he does not pay attention to any threats. Keywords: Saint, narrative, mythology, saint (sacred), Islam